(untitled) (Journal of the College of Basic Education, 2023)
Four Complexes of thiourea derivative (4-methoxy- N-(phenylcarbamothioyl) benzamide) have been prepared by the reaction of 4-methoxybenzoyl isothiocyanate with aniline,then the ligand obtained reacted with (MnII,CoII,CuII,NiII) the resulting complexes were characterized by elemental analysis , FTIR , UV-Vis spectra and melting point. General formula that obtained is [L2MCl2] for all complexes with octahedral geometry, where(L)=(4-methoxy-N(phenylcarbamothioyl)benza-mide) and M= (MnII,CoII,CuII,NiII) .